2010
DOI: 10.1089/pho.2008.2380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laser Photobiomodulation on Cutaneous Wounds Treated with Mitomycin C: A Histomorphometric and Histological Study in a Rodent Model

Abstract: The use of LPBM improves wound healing in subjects treated with MMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…We found that the use of laser and polarized light are effective on improving the healing of diabetic 19,20 and malnourished animals. 21,22 We also found that laser light is capable of improving the healing of drug-induced impairment 23 and on increasing the survival rate of musculocutaneous flaps on both diabetic and nondiabetic animals. 24 We have also studied and shown the influence of laser parameters on the healing of surgical wounds 25,26 as well as on the postoperative period of both surgical and CO 2 laser wounds.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…We found that the use of laser and polarized light are effective on improving the healing of diabetic 19,20 and malnourished animals. 21,22 We also found that laser light is capable of improving the healing of drug-induced impairment 23 and on increasing the survival rate of musculocutaneous flaps on both diabetic and nondiabetic animals. 24 We have also studied and shown the influence of laser parameters on the healing of surgical wounds 25,26 as well as on the postoperative period of both surgical and CO 2 laser wounds.…”
mentioning
confidence: 68%
“…In this case, we have reduction in tissue necrosis and less and precocious inflammatory reaction. 23 In cases in which some therapeutical approach may led to impairment of the healing, such as the use of some drugs, the use of LPT resulted in less inflammation and increased fibroblast proliferation and collagen deposition, favoring healing. 24 Our group has shown, using different models, that association of bone grafts, bone morphogenetic proteins, and guided tissue regeneration does improve the healing of bone tissue.…”
Section: Bone Repairmentioning
confidence: 99%
“…Red light induces differential alterations in 76 genes in wounds treatment 28 . It mainly exerts repairing effects by regulating inflammatory factors, cell growth factors, ROS, and energy production metabolism 29 , 30 . This is mainly because red light itself produces photons that are less likely to scatter and more likely to penetrate tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Low-Intensity Light Therapy (LILT), also known as photobiomodulation, has been reported to modulate a considerable number of biological processes in a significant number of studies. These include increasing wound healing rates [4][5][6][7]; induction of cellular proliferation in multiple cell culture systems; including osteoblasts [8][9][10], fibroblasts [11][12][13], muscle cells and epithelial cells [14,15]; improving the healing time of Herpes labialis infections [16]; increasing ATP synthesis and mitochondrial respiration rates [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%